2001
DOI: 10.1183/09031936.01.17406740
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm fatigue during exercise at high altitude: the role of hypoxia and workload

Abstract: The effect of high altitude (HA) on exercise-induced diaphragm fatigue in normal subjects was examined.Eight normal subjects completed an incremental exercise test at sea level (SL) and at 3,325 m. Before (baseline), during, and after exercise (recovery), maximal transdiaphragm pressure (Pdi,sniff), breathing pattern, and diaphragmatic effort (PTPdi) were measured. Arterialized blood lactate was measured at baseline and during recovery.At maximal exercise (WRmax) Pdi,sniff fell to 72% and 61% of baseline at SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 28 publications
1
27
2
Order By: Relevance
“…Using this technique we found no evidence of exercise-induced central activation failure of the diaphragm. This finding is in agreement with one previous study (Gudjonsdottir et al 2001), although more recent evidence using transcranial magnetic stimulation suggests that central "supraspinal" diaphragm fatigue may occur in response to maximal incremental exercise (Verin et al 2004). …”
Section: 22supporting
confidence: 93%
“…Using this technique we found no evidence of exercise-induced central activation failure of the diaphragm. This finding is in agreement with one previous study (Gudjonsdottir et al 2001), although more recent evidence using transcranial magnetic stimulation suggests that central "supraspinal" diaphragm fatigue may occur in response to maximal incremental exercise (Verin et al 2004). …”
Section: 22supporting
confidence: 93%
“…Additionally, it has been reported that approximately 50% of highly trained individuals exhibit arterial hypoxaemia during high-intensity exercise (Powers et al 1988;Dempsey & Wagner, 1999) and that hypoxaemia worsens the degree of diaphragmatic fatigue (Babcock et al 1995a). However, prior studies did not investigate individuals naturally demonstrating EIAH, and the employment of hypoxic challenge caused not only hypoxaemia but also a higher respiratory muscle effort because of the additional hypoxic stimulus to ventilation (Babcock et al 1995a;Cibella et al 1996;Gudjonsdottir et al 2001). This makes it difficult to isolate the effect of hypoxaemia per se on fatigue.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that hypoxaemia superimposed on high-intensity exercise hastens diaphragmatic fatigue during exercise (Babcock et al 1995a(Babcock et al , 1995b Gudjonsdottir et al 2001). However, hypoxaemia also stimulates ventilation, so that this strategy created not only hypoxaemia but also increased respiratory muscle load, making the role of hypoxaemia difficult to isolate.…”
Section: Respiratory Muscle Loading During the Hi And Lo Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors limiting exercise at altitude may be different from those that limit exercise at sea level and may include diffusion limitation of V O 2 in the alveolus, the work of ventilation, respiratory muscle fatigue, and the possible steal of blood from limb locomotor muscles to respiratory muscles (8,10,30). The perception of dyspnea is also increased during exercise at altitude (5), which may lead to the premature ending of exercise.…”
Section: Discussionmentioning
confidence: 99%